Playwrights for Tomorrow : A Collection of Plays, Volume 9 - Schwartz, Joel; Opper, Don Keith; Schrock, Gladden; Korr, David; Ballet, Arthur H. (Book collections on Project MUSE., 2014)
This is the ninth volume in the continuing series Playwrights for Tomorrow, which makes available collections of plays by dramatists who have participated in the program of the Office for Advanced Drama Research at the University of Minnesota.